Implementation of a novel home energy management system (HEMS) architecture with solar photovoltaic system as supplementary source - Shakeri M.; Shayestegan M.; Reza S.M.S.; Yahya I.; Bais B.; Akhtaruzzaman M.; Sopian K.; Amin N. (Elsevier Ltd, 2023)
Computer architecture; Cost reduction; Electric batteries; Electric power transmission networks; Energy management; Man machine systems; Photovoltaic cells; Smart power grids; Solar power generation; Virtual storage; Demand response; Home energy management systems; Renewable energies; Smart appliances; Smart grid; Energy management systems; algorithm; alternative energy; architecture; control system; cost analysis; demand analysis; electricity supply; instrumentation; photovoltaic system; residential energy; smart grid; solar power